Peircean semiotics and subject indexing: Contributions of speculative grammar and pure logic - Almeida, Carlos Cândido de [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP]; Reis, Daniela Marjorie dos [UNESP] (My University, 2013)
The semiotics of C S. Peirce presents fundamental concepts to discover aspects of the indexing process, including representation and classes of signs. However, we still know little of its theoretical potential for subject indexing. We believe that the main difficulty in the proposals to understand the process of subject indexing based on Peircean semiotics stems from an incomplete interpretation of his semiotic system. This paper attempts to describe the contributions of Peircean semiotics to subject indexing. First, we analyze some of the concepts of the branches of semiotics, after which, we discuss strategies for conceptual approximation. Secondly, and aiming to raise the level of interlocution between the areas, we intend to argue that subject indexing is an inferential process, as explained by the second branch of semiotics. Thus, we seek to go beyond the level of speculative grammar, the first branch of semiotics, to forge a closer link with pure or critical logic, the second branch. We conclude that the indexer's work does not produce a mere reflection of what already exists in documents, but involves an instigating action to discover, through the inferential matrix, the meaning of a text in order to find the subject and the most appropriate subject added entry to the information system.